Knowledge and Acceptance of HPV Vaccination among Women Attending at Out Patient Department of Dhaka Medical College Hospital - Lipi, Lutfa Begum; Rahman, Mohammed Mizanur; Shaha, Nibedita; Sultana, Meher; Ara, Iffat (Bangladesh Medical Journal, 2017)
Vaccination is a part of primary prevention to prevent cervical cancer. The causative agent of cervical cancer is Human Papilloma Virus (HPV). The purpose of this study was to assess the knowledge and awareness regarding cervical cancer prevention by HPV vaccination and acceptance of vaccination among women attending at outpatient department of Dhaka Medical College Hospital. A qualitative study was undertaken using face to face in depth interviews from July 2015 to December 2015. A total of 229 women were included and their mean age was 34.07±7.92 ranging from 18 to 60 years. Awareness and knowledge about cervical cancer was very poor. Only 22.7% participants were aware of HPV vaccination. Knowledge was high among women coming from high socioeconomic condition which was 31.5% (p=0.03). Participants who were highly educated had more knowledge on vaccination about 66.7% (p=0.001). There was a high acceptance (83.8%) of HPV vaccination among participants. The findings focus on the importance of awareness development on cervical cancer and its risk factors. Continuous screening of cervical cancer for early diagnosis and prompt treatment and publicity of awareness development program by mass-media (television, cable line add etc.), poster, billboard and most importantly through health education could play an important role in cervical cancer prevention. Bangladesh Med J. 2017 Jan; 46 (1): 25-31